An analysis of the power market in Vung Tau City - Vietnam - Tu Ngoc Loan; Giap, Van Dang; Pacudan, Romeo B.; Surapong Chiraratananon; Do, Ba Khang; Government of France (Bangkok : Asian Institute of Technology, 1997)
The electricity consumption data of the residential sector in Vungtau City have been gathered and analyzed through a survey of 100 households in four different income groups. Sub-sector and end-use electricity consumption have been estimated. Ownership levels of most essential and common electrical appliances are above 70%. A major growth area that are appliances associated with household income affects to electricity consumption of the residents in Vungtau City. Nevertheless, a scale economies of household size in electricity consumption has been observed that implies the effect of demographic changes to electricity consumption in Vungtau City. Apart from the analysis of the residential electricity consumption patterns, a regression model was established to give the correlations of the factors of household income, number of appliances and household size to the electricity consumption. The results show that a one percent change in the number of appliances causes a 0.58% change in demand for electricity, a one percent change in household income results in 0.12% change in demand for electricity in the same direction, and a one percent change in household size results in 0.18% change in demand for electricity if other variables remained the same respectively. Number of appliances appears to be the best predictor of electricity consumption. Considerable certainty exists about the development of electricity market in Vungtau City. Demand growth for electricity are forecasted to grow at 25% per year in 1996-2000 and 17% in 2000-2005. The consequent capital investment increase of 17.6% per year are required over 1997-2000-2005. The structure of the power sector and electricity tariffs are also discussed in this study. From Vungtau's socio-economic and power market analysis, the market drivers for private participation in the power sector are identified that are consist of capacity expansions, financial constraints, changes of government policies towards privatization, the appearance of Industrial Parks in Vungtau City and the availability of the natural gas resource. In conclusion, the study has assessed the prospects for private participation in the power sector of Vungtau City through the analysis of its real social conditions and the development of electric sector in the city.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Power resources -- Vietnam -- Vung Tau -- Marketing